Modeling and measurement of airplane flutter phenomena on TV broadcasting signal - Wongkeeratikul, A.; Supnithi, P.; Noppanakeepong, S.; Leelaruji, N.; Hemmakorn, N. (My University, 2008)
This paper presents a novel approach to model TV signal due to airplane flutter phenomena. The three components of the modeling are based on 1) Bistatic radar cross sections (RCS) of an ellipsoid, 2) 3-dimensional geometry consideration technique to calculate the distance difference between direct and reflected waves due to airplane, and 3) Ray theory, based on physical and geometrical consideration. Unlike previous works, the model takes into account of realistic parameters such flying height, distance from the airport, flying angle, altitude, aircraft body type and others. The simulation results are then compared with measurement results at 60.75 MHz and 208.75 MHz. The results have shown good agreement between simulation and measurement patterns. © 2008 IEEE.
Keywords: Airplane flutter phenomena; Interference on TV signal; Modeling and measurement on TV signal; Quasi-periodic phenomena